Voltage-sensing domain mode shift is coupled to the activation gate by the N-terminal tail of hERG channels - Tan, Peter S. (The Rockefeller University Press, 2012)
Human ether-a-go-go–related gene (hERG) potassium channels exhibit unique gating kinetics characterized by unusually slow activation and deactivation. The N terminus of the channel, which contains an amphipathic helix and an unstructured tail, has been shown to be involved in regulation of this slow deactivation. However, the mechanism of how this occurs and the connection between voltage-sensing domain (VSD) return and closing of the gate are unclear. To examine this relationship, we have used voltage-clamp fluorometry to simultaneously measure VSD motion and gate closure in N-terminally truncated constructs. We report that mode shifting of the hERG VSD results in a corresponding shift in the voltage-dependent equilibrium of channel closing and that at negative potentials, coupling of the mode-shifted VSD to the gate defines the rate of channel closure. Deletion of the first 25 aa from the N terminus of hERG does not alter mode shifting of the VSD but uncouples the shift from closure of the cytoplasmic gate. Based on these observations, we propose the N-terminal tail as an adaptor that couples voltage sensor return to gate closure to define slow deactivation gating in hERG channels. Furthermore, because the mode shift occurs on a time scale relevant to the cardiac action potential, we suggest a physiological role for this phenomenon in maximizing current flow through hERG channels during repolarization.